Pharmacokinetics, bioavailability, and tissue distribution of MRTX1133 in rats using UHPLC-MS/MS - Lu, Wei; Zeng, Rong; Pan, Meng; Zhou, Yuan; Tang, Huijuan; Shen, Wanying; Tang, Yijun; Lei, Pan (Frontiers in Pharmacology, 2024)
IntroductionMRTX1133 is a selective and reversible small molecule inhibitor of KRAS (G12D), which significantly delays the progression of solid tumors. However, no study on the absorption, distribution, and excretion of MRTX1133.MethodsA fast ultra-high performance liquid chromatography-tandem quadrupole mass spectrometry method was developed for the determination of MRTX1133 in rat plasma, tissue homogenate, and urine. The method applied to the pharmacokinetics, bioavailability, tissue distribution, and excretion of MRTX1133 after oral administration (25 mg/kg) and intravenous administration (5 mg/kg).ResultsThe calibration curve for MRTX1133 in plasma and other homogenates was linear, with r2 > 0.99. The intra- and inter-day accuracies were ranged from 85% to 115% and precision were within ± 10%. The matrix effect and recovery were within ± 15 %. The Cmax of MRTX1133 was 129.90 ± 25.23 ng/mL at 45 min after oral administration. The plasma half-life (t1/2) of MRTX1133 was 1.12 ± 0.46 h after oral administration and 2.88 ± 1.08 after intravenous administration. Its bioavailability was 2.92%. Furthermore, MRTX1133 was widely distributed in all the main organs, including liver, kidney, lung, spleen, heart, pancreas, and intestine. MRTX1133 was still detectable in liver, kidney, lung, spleen, heart, and pancreas after 24 h. The excretion ratio of prototype MRTX1133 through kidney was 22.59% ± 3.22% after 24 h.ConclusionsMRTX1133 was quickly absorbed, and widely distributed in the main organs. This study provided a reference for the quantitative determination of MTRX1133 in preclinical or clinical trials.